Environmental Dilemmas Ethics and decisions - Berry, R.J. (Springer Netherlands, 1993)
This is a book by people who have had to make decisions which affect the environment in which we all live, decisions which sometimes affect the quality of life of millions. It is not an academic disquisition on how to approach decision-making. Most of the chapters are written by scientists who have had to take action or make recommendations on environmental matters in situations where the data are incomplete or choices hedged by factors beyond scientific resolution; the result is that they have had to resolve dilemmas about the proper way forward in the matter. My brief to the authors was to describe issues with which they had been personally concerned, rather than simply select from the vast range of envir- mental problems 'out there'. The only exception to this was Andrew Brennan (Chapter 1), who is a professional philosopher; I asked him to say something about the processes and errors indulged by environmental decision-makers. There is some overlap between chapters, but this is not extensive. I have made no attempt to eliminate it, because the aim has been to present personal points of view, not a systematic account of environmental problems. Similarly, there are important topics which are not covered. Indeed, a critic would complain that a book on environmental dilemmas which does not deal directly with the crucial divide between development and conservation is almost wholly irrelevant; from one point of view, it could be condemned as fiddling while Rome burns.